Potencial de lixiviação do glifosato em um solo da região oeste do Paraná - Gazziero, Andressa (2012)
The indiscriminate use of pesticides in agriculture represents a high risk of environmental contamination. Among these products in Brazil highlights the herbicide glyphosate, widely applied in weed control in soybean and corn. Knowledge of the interactions of herbicides with soil are essential to secure these products recommendations regarding environmental safety. The objective was to evaluate the behavior of glyphosate in soil in the west of Paraná, used in general practice of organic agriculture. For this, experiments were performed using bioassays, in order to generate information to enable the safe use of this herbicide environmental point of view. It was observed that glyphosate is completely adsorbed by the ground on its surface layer, thereby not reaching the underground aquifers.